Relationship Between the Use of Injectable Contraceptives Based on Use at Posyandu Melati - Elizawarda Elizawarda; Maya Handayani Sinaga (Universitas Aisyah Pringsewu, 2023)
In Indonesia, the number of heads of household is 60,349,706 and the number of couples of childbearing age is 36,993,725 as much as 61.29% of the number of heads of families. Nationally, there are 23,361,189 family planning participants, 63.14% of the number of couples of childbearing age in Indonesia. The aim of the study was to use injectable contraceptives based on the length of use at the Melati Posyandu, Sukaraya Village, Pancur Batu District, Deli Serdang Regency 2021. The type of research used was observational analytic by design. cross-sectional study. The population in this study amounted to 25 mothers who accept injections at Posyandu Melati, Sukaraya Village, Pancur Batu District, Deli Serdang Regency 2021. The sampling technique used was purposive sampling. Data analysis used the chi-square test. The results showed that mothers who experienced an increase in body weight of injectable family planning acceptors amounted to 64.0% and those who did not experience an increase were 36.0%. The results of the chi-square test obtained a value of value = 0.017 less than 0.05. Meanwhile, the mothers of injecting family planning acceptors who experienced menstrual cycle irregularities amounted to 76.0% and those who did not experience menstrual disorders were 24.0%. The results of the chi-square test obtained p value = 0.006 less than 0.05. There is a relationship between the use of 3-month injectable contraceptives based on the length of use at the Melati Posyandu, Sukaraya Village, Pancur Batu District, Deli Serdang Regency 2021. Abstrak: Di Indonesia, jumlah kepala keluarga sebanyak 60.349.706 dan jumlah pasangan usia subur 36.993.725 sebanyak 61.29% dari jumlah kepala keluarga. Peserta kb secara nasional sebanyak 23.361.189 sebanyak 63.14% dari jumlah pasangan usia subur di Indonesia.tujuan penelitian untuk mengetahui hubungan penggunaan kontrasepsi suntik berdaraskan lama pemakaian di posyandu melati desa Sukaraya kecamatan Pancur Batu Kabupaten Deli Serdang 2021. Jenis penelitian yang digunakan adalah observasional analitik dengan desain penelitian studi potong lintang (cross sectional). Populasi dalam penelitian ini berjumlah 25 ibu akseptor suntik di posyandu melati desa sukaraya kecamatan Pancur Batu Kabupaten Deli Serdang 2021.teknik pengambilan sampel yang digunakan adalah purposive sampling.analisis data menggunakan uji chi square.hasil penelitian menunjukkan ibu yang mengalami kenaikan berat badan ibu akseptor KB suntik yang berjumlah 64,0% dan yang tidak mengalami kenaikan berjumlah 36,0%. Hasil uji chi square diperoleh nilai p value=0,017 kurang dari 0,05.sedangkan ibu akseptor kb suntik yang mengalami ketidateraturan siklus haid berjumlah 76,0% dan yang tidak mengalami gangguan haid 24,0%.hasil uji chi square diperoleh nilai pvalue=0,006 kurang dari 0,05.ada hubungan antara penggunaan kontrasepsi suntik 3 bulan berdasarkan lama pemakaian di posyandu melati desa Sukaraya kecamatan Pancur Batu Kabupaten Deli Serdang 2021